PLGA Implants for Controlled Drug Delivery and Regenerative Medicine: Advances, Challenges, and Clinical Potential - Hossein Omidian; Renae L. Wilson (Pharmaceuticals)
Poly(lactide-co-glycolide) (PLGA) implants have become a cornerstone in drug delivery and regenerative medicine due to their biocompatibility, tunable degradation, and capacity for sustained, localized therapeutic release. Recent innovations in polymer design, fabrication methods, and functional modifications have expanded their utility across diverse clinical domains, including oncology, neurology, orthopedics, and ophthalmology. This review provides a comprehensive analysis of PLGA implant properties, fabrication strategies, and biomedical applications, while addressing key challenges such as burst release, incomplete drug release, manufacturing complexity, and inflammatory responses. Emerging solutions—such as 3D printing, in situ forming systems, predictive modeling, and patient-specific customization—are improving implant performance and clinical translation. Emphasis is placed on scalable production, long-term biocompatibility, and personalized design to support the next generation of precision therapeutics.